Knowledge, attitude, and practices associated with the diagnosis and management of skin and soft-tissue infections among medical students, residents, and attending physicians - Norman Beatty (Thieme Medical and Scientific Publishers Pvt. Ltd., 2018)
Skin and soft-tissue infections (SSTIs) are commonly encountered by medical students, residents, and trainees. The Infectious Diseases Society of America (IDSA) has updated its recommendations regarding SSTI diagnosis and management in June 2014. We assessed knowledge, attitude, and practices toward diagnosis and management of SSTIs using an online survey. We disseminated the survey to medical students, residents, and attending physicians practicing in family and internal medicine department at a university-based hospital. A total of 103 surveys were completed out of 121 sent (85.1%) between July 2015 and March 2016. There were nine medical questions in the survey. The mean of correct answers was 4.5/9 ± 2.0. Medical knowledge correlated with the level of education (P < 0.001) but not with subspecialty (P = 0.97). Around 35% were familiar with the updated IDSA guidelines pertaining to SSTIs. The majority (85%) responded that the hospital staff would benefit from additional training and 75% agreed that more antibiotic stewardship education is needed. Our study shows that there are significant opportunities for development among students and physicians who encounter SSTIs.